Méritos e limites da teoria da escolha racional como ferramenta de interpretação do comportamento social e político - Mauro Macedo Campos; Hugo Borsani; Nilo Lima de Azevedo (Ciências Sociais Unisinos)
This article presents an approach to rational choice theory, with special emphasis on the capacity of this theory in helping to understand social relations and problems. The aim of this work is to present, in a clear and comprehensive way, the main concepts of the theory of rational choice to a social science audience, which usually sees it as a hard theory. The idea is to highlight the virtues and limitations of this theory. This theoretical approach considers the individual action performed according to autonomous and rational motivations as central to the understanding of social systems, and conceives institutions as the elements that inform and shape the options available to the individual and collective choices. In this sense, rationality is seen as a way of maximizing the preferences of agents who have utilitarian calculation capacity. Their preferences depend on their degree of knowledge or information about the set of opportunities available to them. Assuming this premise of rationality, according to which actions aim to satisfy preferences and not act against them, the theory of rational choice presupposes that individuals are able to make associations between the known and available means and the ends intended by them. Thus, rational choices approach an optimal point, despite their ability to achieve the desired degree of satisfaction. In other words, the use of strict rationality in the field of social choices will not always cause the expected results to be optimal and maximize usefulness or well-being. The rational actions may have unintended negative effects, depending on the informational asymmetries, the position in the decision-making spectrum and/or calculation errors. Revisiting these concepts is the aim of this article, as a way of providing readers with a more accessible understanding of the scope and restrictions of the rational choice theory.